Prevalence and pattern of mental disability using Indian disability evaluation assessment scale in a rural community of Karnataka - Kumar, S. Ganesh (Medknow Publications, 2008)
BACKGROUND: In the present era, mental disability is a major public health problem in the society. Many of the mental disabilities are correctable if detected early. OBJECTIVES: To assess the prevalence and pattern of mental disability. SETTING AND DESIGN: Community-based cross-sectional study. One thousand subjects in all age groups were randomly selected from four villages in Udupi district, Karnataka. MATERIALS AND METHODS: The study was conducted by making house-to-house visits, interviewing, and examining all the individuals in the families selected with pre-designed and pretested questionnaire. STATISTICAL ANALYSIS: Proportions, chi-square test. RESULTS AND CONCLUSION: The prevalence of mental disability was found to be 2.3%. The prevalence was higher among females (3.1%) than among males (1.5%). The prevalence was higher among the elderly age group and illiterates. There is ample scope for community-based rehabilitation of the mentally disabled.